Accumulation of Sellafield-derived radiocarbon (14C) in Irish Sea and West of Scotland intertidal shells and sediments. (January 2016) - Tierney, Kieran M.; Muir, Graham K.P.; Cook, Gordon T.; MacKinnon, Gillian; Howe, John A.; Heymans, Johanna J.; Xu, Sheng
Abstract: The nuclear energy industry produces radioactive waste at various stages of the fuel cycle. In the United Kingdom, spent fuel is reprocessed at the Sellafield facility in Cumbria on the North West coast of England. Waste generated at the site comprises a wide range of radionuclides including radiocarbon ( 14 C) which is disposed of in various forms including highly soluble inorganic carbon within the low level liquid radioactive effluent, via pipelines into the Irish Sea. This 14 C is rapidly incorporated into the dissolved inorganic carbon (DIC) reservoir and marine calcifying organisms, e.g. molluscs, readily utilise DIC for shell formation. This study investigated a number of sites located in Irish Sea and West of Scotland intertidal zones. Results indicate 14 C enrichment above ambient background levels in shell material at least as far as Port Appin, 265 km north of Sellafield. Of the commonly found species (blue mussel ( Mytilus edulis ), common cockle ( Cerastoderma edule ) and common periwinkle ( Littorina littorea )), mussels were found to be the most highly enriched in 14 C due to the surface environment they inhabit and their feeding behaviour. Whole mussel shell activities appear to have been decreasing in response to reduced discharge activities since the early 2000s but in contrast, there is evidence of continuing enrichment of the carbonate sediment component due to in-situ shell erosion, as well as indications of particle transport of fine 14 C-enriched material close to Sellafield. Highlights: We measure 14 C activity in shells and sediment at sites on the UK west coast. Mussel shell activity varies in response to average 14 C discharges from Sellafield. Shell activities reflect species feeding habits and ecological niche. NE Irish Sea inorganic sediment activity will gradually increase. Increases in sediment activity will occur at remote sites on the Scottish west coast.